2015
DOI: 10.1007/s11552-014-9737-4
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal Allograft Arthroplasty for the Treatment of Trapeziometacarpal Arthritis of the Thumb

Abstract: BackgroundArthritis at the trapeziometacarpal joint of the thumb is common. Several surgical options exist showing favorable results. We report the outcomes after interposition of allograft knee meniscus for thumb trapeziometacarpal arthritis.MethodsTwenty-three patients (25 thumbs) had surgery for thumb trapeziometacarpal arthritis using knee meniscal allograft tissue. Eleven thumbs had a minimum follow-up of 24 months, 2 thumbs had a minimum of 12 months, and 12 thumbs had less than 6 months. Disabilities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Surgical treatments for thumb CMC OA include first metacarpal osteotomy, trapezial osteotomy, arthrodesis, trapeziectomy, ligament reconstruction and tendon interposition (LRTI), hematoma distraction arthroplasty, bone or soft tissue interposition arthroplasty, and joint-replacement arthroplasty. 4,5,[8][9][10][11]13,15,21,22,[24][25][26] All these techniques have been found to mitigate symptoms and improve function, but an "ideal" procedure that not only alleviates pain but also preserves the length, stability, strength, and normal function of the thumb, while avoiding the morbidity associated with tendon harvest, has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatments for thumb CMC OA include first metacarpal osteotomy, trapezial osteotomy, arthrodesis, trapeziectomy, ligament reconstruction and tendon interposition (LRTI), hematoma distraction arthroplasty, bone or soft tissue interposition arthroplasty, and joint-replacement arthroplasty. 4,5,[8][9][10][11]13,15,21,22,[24][25][26] All these techniques have been found to mitigate symptoms and improve function, but an "ideal" procedure that not only alleviates pain but also preserves the length, stability, strength, and normal function of the thumb, while avoiding the morbidity associated with tendon harvest, has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…At approximately $1200 USD for a full meniscus, it is comparable to other currently used implants, for example, the pyrocarbon spacer, PI2 (Tornier Bioprofile, Grenoble, France) which retails for € 930 European, the Arthrex mini-tightrope (Arthrex, Inc, Naples, Fla.) at approximately $1000 USD, the GraftJacket acellular dermal matrix (Wright Medical Group, Memphis, Tenn.) between $1000 and 3000 USD, and the titanium hemiarthroplasty implant at approximately $2000 USC (Wright Medical Group). 24 , 55 Tailored smaller MAT sizes specific to the hand and small digit joint space may further reduce the cost of the meniscus allograft and maximize the use of the donated human tissue. Studies have demonstrated a cost-effectiveness of arthroplasty using pyrocarbon implants in rheumatoid patients with MCP joint arthroplasty in terms of repeat operations and overall utilization of the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Although predominantly used in the lower extremity, Nanavati et al 23 first described the use of MAT for proximal carpectomy in the hand. More recently, Shapiro et al 24 described the use of MAT for interposition arthroplasty in trapeziometacarpal arthritis, and Hoang et al 25 described it for resurfacing of metacarpal phalangeal and proximal interphalangeal joints of the hand. However, further studies regarding clinical outcomes are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…28 While predominantly used in the lower extremity, Nanavati et al 30 first described the use of MAT for proximal carpectomy in the hand. More recently, Shapiro et al 31 described the use of MAT for interposition arthroplasty in CMC arthritis, and Hoang et al 32 described it for resurfacing of metacarpal phalangeal and proximal interphalangeal joints of the hand. However, further studies regarding clinical outcomes, including strength and range of motion measures, as well as patient-reported pain and disability scores, are lacking.…”
Section: Introductionmentioning
confidence: 99%